Performances of grooved plates falling film absorber. (1st November 2017) - Michel, Benoit; Le Pierrès, Nolwenn; Stutz, Benoit
Abstract: This study presents a new plate-type falling film absorber design, consisting in a vertical grooved falling film absorber. The grooves are designed to obtain good absorber plate wettability, even at a low solution flow rate, resulting in a laminar solution flow regime. Using experimental and numerical tools, the vapor absorption on a LiBr falling film solution is characterized for different operating conditions. The impact of absorber length, cooling water inlet temperature, absorber water vapor pressure, solution inlet temperature, LiBr mass fraction and flow rate is investigated. Experimentally, a high absorption rate is achieved: as high as 7·10 −3  kg s −1  m −2 . Moreover, a 1D stationary model of water vapor absorption in a laminar vertical falling film is introduced and validated. Numerical investigations allow defining the absorber effectiveness for a wide range of operating conditions. Highlights: A new vertical grooved falling film absorber using H2 O/LiBr was developed. A wide range of solution conditions was tested (Ts  = 20–40 °C; Re = 50–300; xi  = 57–60%w ). Absorption rates as high as 7·10 −3  kg s −1  m −2 were obtained. A 1D stationary model of water absorption on falling film was developed and validated.